Developing Career Development Profiles of Student-Athletes: A Comparison with Non-Athletes - Wooten, Jr., H. Ray; Usher, Clair H.; Osborne, W. L. (My University, 1994)
Student-athletes' and non-athletes' scores on several career-related assessments were compared. During the 1990-91 academic year at a medium-sized, state-supported university in the South, a sample of 41 student-athletes (83% males and 17% females) and 178 non-athletes (29% males and 71% females) completed the Values Scale (Super & Nevill, 1985b), Career Development Inventory (Super, Thompson, Lindeman, Jordaan, & Myers, 1981), and Salience Inventory (Super & Nevill, 1985a). Completion of these instruments was required for a semester-long, three-credit course in career/life planning. The student-athletes were non-revenue scholarship athletes representing a NCAA Division II institution in soccer, basketball, and tennis. Both groups contained students representing all class ranks, with a majority in both groups being white (93% of the student-athlete group and 69% of the non-athlete group. Results of two-way ANOVAs indicated that student-athletes highly value physical activity and spend more time in leisure activities than non-athletes. Only one significant gender effect was found: females had a higher score on the combined knowledge scale (M = 100.29) than males (M = 85.16) (F(1, 138) = 8.43, p < .006). The combined knowledge scale score is a linear combination of scores in decision-making and world-of-work information. This result indicates that females may be better able to apply career development principles to decision-making scenarios as well as demonstrate more knowledge of what it takes to get a job and succeed. No differences in career maturity scores were found. Implications for programming to accommodate the special needs of student-athletes are discussed.
Keywords: career development; Division II; sex/gender; non-athlete students